A study on the implementation of intelligent vehicle in Malaysia / Ahmad Farid Najmuddin - Ahmad Farid, Najmuddin (2003)
Most drivers in Malaysia are facing problems where they have to give full concentration on driving through out their journey to the desired destination. There are a few factors that contribute to road accidents or crashes in Malaysia. Some factors are caused by the driver's faulty and some factors are caused by the lack of features provided by the vehicle itself. In the end, the number of road crashes increased and even worst the number of death and injuries also increased. This research intends to investigate the problems faced by most drivers while they are on the road. At the same time, this research also investigates the commercially available intelligent products and the user requirements toward it. Besides that, this research has proposed the intelligent vehicle architecture that suits the local need. Perhaps, the findings of this research are able to help people in the future.